Implementation of Magic Book to Improve Critical Thinking and Mathematical Communication Abilities of Elementary School Students - Hanim Faizah; Eko Sugandi; Ninik Mutianingsih; Lydia Lia Prayitno (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2025)
The use of digital mathematics teaching materials is one alternative to improve students' 21st century skills in mathematics learning. Mathematics Digital Creative (MAGIC) Book is one of the digital teaching materials that has been developed to improve students' critical thinking and mathematical communication skills. This quantitative research uses an experimental approach with a one-shot case study design. The subjects used in this study were four schools in the Surabaya and Sidoarjo areas, with a sample size of 65 students. The results of data analysis show that the average value of students' critical thinking skills is 74.29 with the highest value of 91.67 and the lowest value of 43. The average value of mathematical communication skills is 97.9 and the lowest is 40. The t-statistical test found that the t-count value was 4.604 with a degree of freedom of 128 and sig. of 0.037 which is greater than the value of α = 0.05 and the mean difference value of 9.73. It can be concluded that the application of MAGIC Book in mathematics learning in Elementary Schools can provide positive results in improving students' critical thinking and mathematical communication skills, especially in the main material of Greatest Common Divisor (GCD) and Least Common Multiple (LCM).